DEVELOPMENT AND VALIDATION OF A BIOANALYTICAL RP-HPLC METHOD FOR AZILSARTAN MEDOXOMIL WITH LIQUID-LIQUID EXTRACTION - Karpe, Snehal; Sonawane, Sandeep; Rahade, Priya; Kshirsagar, Sanjay (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: There are many analytical methods available for estimation of Azilsartan medoxomil in biological samples and for pharmaceutical preparations. However, no specific RP-HPLC method with UV detection based on liquid-liquid extraction technique is available for estimation of Azilsartan medoxomil in human plasma. Methods: A simple, rapid and accurate RP-HPLC with UV detection method was developed and validated as per US-FDA guidelines for the estimation of Azilsartan medoxomil in spiked human plasma using liquid-liquid extraction technique. Results: Azilsartan medoxomil was well resolved from human plasma interference and internal standard (Aceclofenac) using C 18 (250 Ã— 4.6 mm, 5 Î¼) column with methanol: 20 mm phosphate buffer (pH 3.0), (70: 30 %, v/v) as mobile phase, at a flow rate of 1 ml/min. The detection was performed at 249 nm. The calibration curve was found linear in the range of 500-16000 ng/ml. During calibration experiments, the heteroscedasticity was minimized by using weighted least square regression model with weighing factor 1/xÂ². In accuracy and precision studies, intra-day and inter-day, % relative error was found betweenÂ±15 and % RSD was less than 15 %. Stability experiments indicated that the drug remained stable after three freeze-thaw cycles. Conclusion: A simple, rapid and accurate RP-HPLC method with UV detection was developed and validated for estimation of Azilsartan medoxomil based on liquid-liquid extraction technique. The developed method meets the requirements of US-FDA guidelines. Also the developed method does not require expensive chemicals and solvents and does not involve complex instrumentation, hence it is economic. Â